Role of FDG PET-CT in Takayasu arteritis: sensitive detection of recurrences - Tezuka, Daisuke; Haraguchi, Go; Ishihara, Takashi; Ohigashi, Hirokazu; Inagaki, Hiroshi; Suzuki, Jun-ichi; Hirao, Kenzo; Isobe, Mitsuaki (JACC. Cardiovascular imaging, 2012)
The aim of this study was to investigate whether the maximum standardized uptake value (max SUV) of (18)F-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/computed tomography (CT) provides a quantitative indication of disease activity in Takayasu arteritis (TA) cases. The clinical value of FDG-PET for assessing TA has been investigated. Clinical evaluation of disease activity is often difficult, because most patients develop recurrent inflammation while receiving corticosteroid treatment. Thirty-nine TA patients underwent FDG-PET/CT at Tokyo Medical and Dental University from 2006 to 2010 (35 women and 4 men; median age, 30 years). Disease activity was defined according to National Institutes of Health criteria. Biomarkers including C-reactive protein and erythrocyte sedimentation rate were measured. Forty subjects without vasculitis served as control subjects. The max SUV was significantly higher in active than in inactive cases and control subjects (active [n = 27], median value, 2.7 vs. inactive [n = 12], 1.9; control [n = 40], 1.8; p < 0.001 each). Given a max SUV cutoff of 2.1, sensitivity for active-phase TA was 92.6%, specificity 91.7%, positive predictive value 96.2%, and negative predictive value 84.6%. In receiver-operating characteristic curves comparison, max SUV was superior to C-reactive protein (p < 0.05) and erythrocyte sedimentation rate (p < 0.05). Max SUV was significantly higher in relapsing on treatment cases (n = 17) than in stable on treatment cases (n = 12) (median value, 2.6 vs. 1.9; p < 0.001). FDG-PET/CT is useful for detection of active inflammation not only in patients with active TA before treatment but also in relapsing patients receiving immunosuppressive agents. The max SUV is useful for assessing subtle activity of TA with high sensitivity.